Isotopic composition of natural and synthetic chlorate (δ18O, Δ17O, δ37Cl, 36Cl/Cl): Methods and initial results. (July 2021) - Jackson, W. Andrew; Brundrett, Maeghan; Böhlke, J.K.; Hatzinger, Paul B.; Mroczkowski, Stanley J.; Sturchio, Neil C.
Abstract: Natural chlorate (ClO3 − ) is widely distributed in terrestrial and extraterrestrial environments. To improve understanding of the origins and distribution of ClO3 −, we developed and tested methods to determine the multi-dimensional isotopic compositions (δ 18 O, Δ 17 O, δ 37 Cl, 36 Cl/Cl) of ClO3 − and then applied the methods to samples of natural nitrate-rich caliche-type salt deposits in the Atacama Desert, Chile, and Death Valley, USA. Tests with reagents and artificial mixed samples indicate stable-isotope ratios were minimally affected by the purification processes. Chlorate extracted from Atacama samples had δ 18 O = +7.0 to +11.1‰, Δ 17 O = +5.7 to +6.4‰, δ 37 Cl = −1.4 to +1.3‰, and 36 Cl/Cl = 48 × 10 −15 to 104 × 10 −15 . Chlorate from Death Valley samples had δ 18 O = −6.9 to +1.6‰, Δ 17 O = +0.4 to +2.6‰, δ 37 Cl = +0.8 to +1.0‰, and 36 Cl/Cl = 14 × 10 −15 to 44 × 10 −15 . Positive Δ 17 O values of natural ClO3 − indicate that its production involved reaction with O3, while its Cl isotopic composition is consistent with a tropospheric or near-surface source of Cl. The Δ 17 O and δ 18 O values of natural ClO3 − are positively correlated, as are those of ClO4 − and NO3 − from the same localities, possibly indicating variation in the relative contributions of O3 as a source of O in the formation of the oxyanions. Additional isotopic analyses of ClO3 − could provide stronger constraints on its production mechanisms and/or post-formational alterations, with applications for environmental forensics, global biogeochemical cycling of Cl, and the origins of oxyanions detected on Mars. Highlights: Developed and validated method for purification and isotopic analyses of chlorate. Natural chlorate isotopic composition is distinct from anthropogenic chlorate. Natural chlorate from the Atacama and Death Valley have distinct isotopic compositions. Isotopic compositions of natural chlorate are different from those of coexisting perchlorate. Natural chlorate is partially formed from reactions with ozone.